Dynamic changes of bacterial community during the composting of oil palm empty fruit bunches (OPEFB) as analyzed by denaturing gradient gel electrophoresis (DGGE) analysis - Jong, Bor Chyan; Goh, Chee Meng; Liew, Pauline Woan Ying; Thong, Kwai Lin (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study cultivation-independent approach was performed to characterize and understand the bacterial community dynamics during the oil palm empty fruit bunches (OPEFB) composting process. OPEFB was composted in a compost heap of 1m × 1m × 1m. During the process, bacterial community structure in specific composting time were characterized by denaturing gradient gel electrophoresis (DGGE) analysis based on the hypervariable V3 region of 16S rRNA gene. The DGGE banding patterns revealed significant change in the bacterial community structure throughout the composting process. A total of 38 bands were selected for sequencing analysis. Majority of the DGGE bands’ sequences were related to known counterparts with low percentage of identity indicating novel composting bacterial populations. These DNA sequences were related to culturable relatives of Firmicutes, Proteobacteria, Acidobacteria, Bacteroidetes, Fibrobacteres and Chloroflexi. In general, distinctive predomination by Firmicutes followed by succession by Proteobacteria were revealed during the OPEFB composting process. Information attained in this study may be useful for improving the efficiency of OPEFB composting by indigenous bacterial population. The diverse sequences from known bacteria indicated novelty in the composting bacterial populations and potentially their functions.